The influence of culture on the sustainable livelihoods of households in rural tourism destinations. Issue 8 (3rd August 2021) - Ma, Xiaolong; Wang, Rong; Dai, Meiling; Ou, Yanghong
Abstract: This paper describes a modification of the Sustainable Livelihoods Framework (SLF) and reports the effects of culture on the sustainable livelihoods of households in a typical rural tourist site in Wuyuan county, Jiangxi province, China. Different from the previous studies, this paper highlights the role of cultural factors in households' sustainable livelihoods. The modified SLF can be used as a possible theoretical model to comprehensively characterise the sustainable livelihoods of households in tourism destinations with rich cultural resources. Results show that traditional culture significantly impacts locals' thoughts and behaviours and is an indispensable livelihood asset for households. The commercial value of traditional culture has gained prominence in response to shifts in modern tourists' preferences. Most households draw on their past to generate intangible and tangible cultural products to attract tourists and achieve their livelihood goals. The utilisation of tangible cultural resources and intangible cultural heritage to develop rural tourism promotes changes in the livelihood strategies of households. It can enhance locals' financial, human, and social capital. However, rural tourism development has made cultural preservation a potential source of livelihood vulnerability for households in the study area. Regulations may help reduce the adverse livelihood outcomes of rapid tourism development.